2014
DOI: 10.1186/s13000-014-0166-z
|View full text |Cite
|
Sign up to set email alerts
|

An immunohistochemical study of canine spontaneous gastric polyps

Abstract: BackgroundGastric polyps (GP) are characterised by luminal overgrowths projecting above the plane of the mucosal surface that can be classified as non-neoplastic and neoplastic lesions. In humans, recent studies have drawn attention to the malignant potential of some of these lesions. However, gastric polyps are uncommon lesions in dogs.FindingsIn this study, the presence of Helicobacter spp., the cellular proliferative activity, potential phenotypic alterations, COX-2 and p53 expression in canine spontaneous … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
11
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 20 publications
3
11
0
Order By: Relevance
“…That is, the results of Tn and STn immunoexpression recorded in canine GPs were very similar to those obtained in the normal canine gastric mucosa. These evidences reinforce previous results achieved by our group, which concluded that canine GPs do not present relevant molecular alterations, thus should be considered merely proliferative and hyperplastic lesions, with lack of features suggestive of neoplastic transformation 23 …”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…That is, the results of Tn and STn immunoexpression recorded in canine GPs were very similar to those obtained in the normal canine gastric mucosa. These evidences reinforce previous results achieved by our group, which concluded that canine GPs do not present relevant molecular alterations, thus should be considered merely proliferative and hyperplastic lesions, with lack of features suggestive of neoplastic transformation 23 …”
Section: Discussionsupporting
confidence: 91%
“…Gastric polyps (GPs) are incidental findings in both human and dogs 19,20 . A previous study conducted by our group demonstrated that unlike in humans, 21,22 canine GPs do not display some molecular features suggestive of malignant transformation 23 …”
Section: Introductionmentioning
confidence: 78%
“…In these dogs, hypergastrinaemia secondary to atrophy may be important in carcinogenesis . Unlike in humans, precursor lesions are not frequently described in dogs that develop GC and no convincing relationship could be demonstrated between gastric polyps that are sporadically identified, Helicobacter , and GC . H .…”
Section: Introductionmentioning
confidence: 88%
“…3,4 Reported tumors include adenocarcinomas, leiomyosarcomas, lymphomas, leiomyomas, polyps, adenomas, gastrointestinal stromal tumor, plasmocytoma, mast cell, and fibrosarcoma. 2,[5][6][7][8][9] In veterinary medicine, standard imaging modalities used to characterize and stage gastric masses include radiography, ultrasonography, and endoscopy. 9,10 On radiography, gastric masses may be recognizable if the stomach is filled with air.…”
Section: Introductionmentioning
confidence: 99%